Endobiotic microalgae in molluscan life - Yulia Sokolnikova (Fisheries and Aquatic Sciences, 2022)
Endobiotic microalgae inhabit various groups of organisms, including bivalves. In this group, the association between the giant molluscs Tridacna and Symbiodinium is one of the most recognizable. This consortium allows hydrobionts to survive in oligotrophic waters by regulating their metabolism. The available research has provided an understanding of the interaction and adaptation of these symbionts, but the problem of the beginning of the formation of these relationships remains unresolved. In the case of Tridacninae, symbiosis is essential for the survival of bivalves, in contrast to representatives of the Mytilidae and the Coccomyxa found in them. A few works devoted mainly to the morphological aspects of invasion have shown that endobiont causes inflammation and pathology. Having data to clarify the exact “diagnosis” of the interaction of these organisms is not enough. It is possible that the relationship between bivalves and Coccomyxa is in the early stages of being established, which may lead to mutualism or parasitism in the future. We assume that the analysis of works on the symbiosis of Symbiodinium and bivalves will facilitate the course of research for the less studied Coccomyxa and their hosts. By postulating the Coccomyxa represent a unique evolutionary model for the formation of a symbiotic system, it is possible to use this system to study the interaction of organisms during their initial contact. The identified signalling pathways and mechanisms that allow the photobionts to evade host immunity can be useful for constructing new forms of symbiosystems.